DESIGN OF UD BRICK RAW MATERIAL PREDICTION APPLICATION. INARA - Adri, A. Ahmad Zaki; Mallisza, Danyl (JENTIK, 2024)
Raw material data processing system is a very important thing in trading business. A computerized system is needed that can make predictions that are more effective, efficient and balanced with adequate human resources. UD.INARA does not yet have a system that can predict the need for brick raw materials. Because in the process of processing raw brick material data still uses manual predictions which are of course inaccurate, so that the process of ordering customers to calculating raw materials is not effective and efficient. The system design uses the SDLC (System Development Life Cycle) waterfall method which consists of five stages, namely 1) planning, 2) analysis, 3) design, 4) implementation, 5) maintenance. System modeling uses UML (Unified Modeling Language) to describe visually, which is then implemented using the Hypertext Preprocessor (PHP) programming language with MySQL database as the database used. This design produces a data processing application for ud.inara brick raw materials that is effective and efficient in the process of predicting raw materials. This system can also generate accurate raw material reports. The design of a data processing application for brick raw materials is expected to improve UD.INARA's performance, to be more productive and efficient in providing services to customers.